Монголын нууц товчооны нэгэн хэллэгийн англи орчуулгын тухайд: On English translations of a specific expression in the “Secret History of the Mongols” - Д., Отгонтуяа (Mongolian Studies, 2023)
In this article, author deals with the expression “ke’eli niketen keke qaqcatan” in the paragraph §121 of the Secret History of Mongols. The Mongolian and English translations are also examined. According to the author, ke’eli and keke have relationship through their translations of ‘container’ and ‘thing contained’ respectively. Analyzing the above explanations then translates as: ’Qorci came, saying: “We were born of the woman who captured by Bodoncar Boqdo; we were Coming from the same womb and Carried by the same mother.